2019
DOI: 10.1039/c8ta10130b
|View full text |Cite
|
Sign up to set email alerts
|

Lone-pair effect on carrier capture in Cu2ZnSnS4solar cells

Abstract: The performance of kesterite thin-film solar cells is limited by a low open-circuit voltage due to defect-mediated electron-hole recombination. We calculate the non-radiative carrier-capture cross sections and Shockley-Read-Hall recombination coefficients of deep-level point defects in Cu 2 ZnSnS 4 (CZTS) from first-principles. While the oxidation state of Sn is +4 in stoichiometric CZTS, inert lone pair (5s 2 ) formation lowers the oxidation state to +2. The stability of the lone pair suppresses the ionizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 71 publications
3
71
0
Order By: Relevance
“…Trapping is also observed in TRTS measurements [88,93]. The mechanism and defects involved with this minority carrier trapping is an active area of research [94][95][96][97]. Similar results can be expected from photoconductivity decay, photovoltage decay, and related measurements, which probe the decay of excess carriers.…”
Section: Measuring a Sub-picosecond Lifetime In Cztssesupporting
confidence: 59%
See 1 more Smart Citation
“…Trapping is also observed in TRTS measurements [88,93]. The mechanism and defects involved with this minority carrier trapping is an active area of research [94][95][96][97]. Similar results can be expected from photoconductivity decay, photovoltage decay, and related measurements, which probe the decay of excess carriers.…”
Section: Measuring a Sub-picosecond Lifetime In Cztssesupporting
confidence: 59%
“…Next, grain boundary recombination has been reported to contribute to bulk recombination of carriers [90]. Lastly, a more traditional non-radiative recombination mechanism through deep defects in the bulk are expected to play an important role in explaining the significant non-radiative losses measured in kesterites [90,95]. A relative comparison of the various loss mechanisms discussed here-in is illustrated in the energy band diagram shown in figure 4.…”
Section: Determining the Origin Of Rate Limiting Recombinationmentioning
confidence: 95%
“…Germanium (Ge) is probably one of the most suitable and interesting group IV elements for adding into the kesterite structure, in particular at the Sn-sites. Considering the most stable oxidation states of these two elements, +4 is more likely to occur with Ge than with Sn [103], thus avoiding presence of potentially harmful +2 oxidation states [104]. Additionally, a bandgap range from 1.0 to 2.25 eV is possible with the Cu 2 Zn(Sn 1-x Ge x )(S 1-y ,Se y ) 4 alloy [97,[105][106][107].…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…Research efforts to identify intrinsic defect(s) negatively affecting the minority carrier lifetime and diffusion length of the kesterite absorbers should be intensified. For instance, a recent theoretical study has suggested that the sulfur vacancy V S that is stabilized by the presence of Sn 2+ can act as a non-radiative site [104,177]. This should be verified experimentally, and if confirmed, efforts can be targeted to test doping/alloying strategies that compensate these defects and stabilize the normal-valence oxidation state of Sn 4+ .…”
Section: What We Need To Learnmentioning
confidence: 99%
“…While in the past, only the position of the defect levels in the band gap were accessible, recent progress has made prediction of carrier capture and recombination rates possible from first-principles [73]. In this way the most detrimental defects can be identified, for example Sn Zn and V S are predicted to act as giant carrier traps in Cu 2 ZnSnS 4 [74]. However, such calculations are challenging in terms of human effort and calculation time so they have been performed for very few systems.…”
Section: Latest Progresses In Selected Topic: Modeling Of Emerging Pvmentioning
confidence: 99%